A case report of a complete degloving injury of the penile skin. (2016) - Aineskog, Helena; Huss, Fredrik
Highlights: A split-thickness skin graft gave functional and cosmetically acceptable results to this completely degloved penis. A 1:1 mesh made it possible to use any direction of the graft and achieve a good cosmetic result and can be recommended. The risk of having to go through repetetive surgery in the genital area, made smoking cessation possible for this specific patient. Abstract: Introduction: Male genital degloving injuries are unusual and rarely caused by animal bite. Usually patients attend health care immediately if bitten in the genital area. Prophylactic antibiotics is routinely used (Gomes et al., 2000). A penile degloving usually begins just proximal of the coronal line and progress down to the base of the shaft. Deep erectile tissue and the spermatic cord are seldom damaged and the endogenous skin of glans usually survives (Brown and Fryer, 1957; Morey et al., 2004; Finical and Arnold, 1999). Presentation of case: A heavily smoking man with a previous history of bladder cancer presented himself to the emergency department 24 h after a dog bite degloved his penis. The avulsed skin was necrotic and subsequently excised. Antibiotic treatment was started. A bacterial swab was found positive for canine oral flora. The skin defect was closed using a 1:1 meshed split thickness skin graft from the inner thigh. Smoking cessation was encouraged. At the three month follow up the patient expressed satisfaction with both cosmetic and functional result and was now non-smoking. Discussion: Several approaches to reconstruct penile skin exist. Split thickness skin graft has been lifted as a preferable alternative (Brown and Fryer, 1957; Finical and Arnold, 1999; Paraskevas et al., 2003)[5] . In this case, the avulsed skin was necrotic and could not be used. A 1:1 meshed split-thickness graft was chosen with excellent results. Conclusion: 1:1 mesh of the graft can be recommended for easy attachment with a good functional and esthetical result. The potential risk of losing intimacy appearance or having to go through repeated procedures in the genital area motivated smoking cessation for this patient.